The Stages of Formation of Staging Classical Works in The Years of Independence (2000 - 2020 On the Example of Karakalpak State Academic Musical Drama Theater Named After Berdakh) - Abiyev Sultanbek Kalbayevich (Zien Journals, 2022)
Theater is considered to be one of the central components of the Uzbek culture. And the adoption of the independence of the Republic gave rise to the formation of national works. The value of the theater in instilling love for the motherland and humanistic values have been admitted by many outstanding people. The following article is devoted to the stages of formation of staging classical works in the years of independence in the example of Karakalpak State Academic Musical Drama Theater named after Berdakh.
Keywords: theatre; drama; genre; epoch